PENGUJIAN BAKTERI PGPR DALAM MENINGKATKAN PERKECAMBAHAN BENIH JAGUNG PULUT - Yuaner, Yuaner; Rianto, Fadjar; Abdurrahman, Tatang (Agros Journal of Agriculture Science, 2024)
PGPR bacteria used in waxy corn seeding can a role in increasing seed vigor and power of seed germination. The purpose of the study was to test the ability of PGPR to improve the quality of waxy corn seeds. The study was conducted in Pontianak City, West Kalimantan in August 2023. Germination testing due to PGPR bacteria was carried out using 2 levels of treatment, namely seed soaking in sterile distilled water (control) and seed soaking treatment in PGPR bacterial suspension. The results showed that the use of PGPR bacteria did not show any increase in the quality of waxy corn seeds, as the vigor index, growth simultaneity, power of germination, growth rate and length of sprout roots were lower compared to the quality of waxy corn seeds in the treatment without PGPR. PGPR can increase the growth of corn seedlings, in root weight and the upper part of plant sprouts.